Personal Values and Organizational Commitment among Administrative Employees of a Public University - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan; Idris, Sharifah (International Journal of Asian Social Science, 2021)
The university management found that some issues arose among their administrative employees on organizational commitment due to personal values. The management sees that the issues need to be curbed as they will involve organizational performance. Thus, this paper intends to understand the relationship and the impact between personal values consisted of work value, wisdom, loyalty, and responsibility toward organizational commitment consisted of affective commitment, continuance commitment, and normative commitment among employees in the public university. The population was administrative employees of a public university in Kedah, Malaysia consisted of 320 employees. Self-administered questionnaires were distributed among administrative employees. The study discovered there was a strong relationship between personal values and organizational commitment among administrative employees in the public university. The administrative employees indicated a strong and moderate relationship on their personal values toward organizational commitment. Finally, the administrative employees indicate that personal values, in general, had an impact on their organizational commitment.